2012
DOI: 10.1051/0004-6361/201218988
|View full text |Cite
|
Sign up to set email alerts
|

HD 96446: a puzzle for current models of magnetospheres?

Abstract: Context. Oblique magnetic dipole fields have been detected in Bp stars for several decades, and more recently also in normal massive stars. In the past decade, it has been established that stellar magnetospheres form through the channelling and confinement of an outflowing stellar wind by the stellar magnetic field. This explains specific properties of magnetic massive stars, such as their rotationally modulated photometric light curve, Hα emission, UV spectra, and X-ray emission. Aims. In the framework of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 36 publications
10
59
2
Order By: Relevance
“…Neiner et al 2012), and pulsations are known to have an impact on the analysis of the presence of a magnetic field and its strength (e.g. Schnerr et al 2006;Hubrig et al 2011a), we verified that no change in the line profile shape or radial velocity shifts are present in the obtained sub-exposures.…”
Section: Potsdam Reduction and Analysissupporting
confidence: 65%
“…Neiner et al 2012), and pulsations are known to have an impact on the analysis of the presence of a magnetic field and its strength (e.g. Schnerr et al 2006;Hubrig et al 2011a), we verified that no change in the line profile shape or radial velocity shifts are present in the obtained sub-exposures.…”
Section: Potsdam Reduction and Analysissupporting
confidence: 65%
“…These features are often detected in short-period binaries or pulsating stars. Neiner et al (2012) report the analysis of similar spurious signatures observed in the null profiles of the magnetic star HD 96446. They showed that the radial velocities of the spectral lines have changed between the four sub-exposures of one polarised observation, and that such rapid changes (relative to the exposure time) in the radial velocities of the spectral lines, with an amplitude of about 7 km s −1 , create spurious signatures in the null profiles.…”
Section: Origin Of the Lsd V Signaturesmentioning
confidence: 84%
“…Neiner et al 2012, and references hereinafter). Our findings are (4) and (6): surface gravity of the stars obtained from Strömgren and Geneva photometry.…”
Section: Spectrum Description and Peculiaritiesmentioning
confidence: 99%
“…Therefore, it is not possible to verify the plausibility of the ∼0.5 d period solution. However, as shown by Neiner et al (2012), rapid RV variations that occur over the timescale of a single polarimetric sequence can induce detectable signatures in the diagnostic null profiles. These signatures result from residual polarisation signals that were not properly cancelled during processing because of the RV shifts.…”
Section: Radial Velocity Variationsmentioning
confidence: 98%